Workshop for Kolej Komuniti Rompin - Sarah, Zulkiple (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
28-29 June 2012. A two-day Research Report Writing Workshop had forty academic staff from Kolej Komuniti Rompin at UMP. Four experienced speakers, Associate Professor Dr Ainol Haryati Ibrahim, Dr Nik Aloesnita Nik Mohd Alwi, Dr Norrihan Sulan and Dr Zailin Shah Yusoff were invited to share their knowledge and experiences in researc expositions and practices.